Warm moxibustion scraping therapy and nursing management for a cervical spondylosis patient who suffered from neck and shoulder pain and motion limitation (温灸刮痧技术治疗1例项痹病颈肩疼痛伴颈肩活动受限患者的护理体会) - TIAN Chenchen (田晨晨); LI Yuxin (李玉欣); TANG Ling (唐玲); DENG Jianhua (邓建华) (Association of Integrative Nursing, 2023)
This paper reviewed the treatment effects observation of warm moxibustion scraping therapy and nursing measures for a cervical spondylosis patient who suffered from the neck and shoulder pain and motion limitation. Based on the Traditional Chinese Medicine theory and syndrome differentiation, the warm moxibustion scraping therapy was carried out to enhance the immunity, relieve the pain and improve the motion of the joint. (本文总结1例项痹病颈肩疼痛伴颈肩活动受限患者采用温灸刮痧疗法的护理经验。基于中医基础理论和辨证施护, 通过开展温灸刮痧, 提高患者机体抵抗力, 缓解疼痛, 改善症状, 提高肩关节活动度。)